Применение метода последовательных приближений для численного анализа одной краевой задачи теории горения - Васильева, Ю. В. (ХНУРЕ, 2013)
Рассматривается задача о тепловом самовоспламенении химически активной смеси газов в сосуде. Решение нелинейной краевой задачи сводится к решению последовательности линейных краевых задач. На каждом шаге итерационного процесса используются методы R-функций и Ритца. In this work the Dirichlet problem for an elliptical equation with exponential nonlinearity is considered. The delivered boundary value problem is a mathematical model of the task about thermal inflaming. The solution of a non-linear boundary value problem is consolidated to the solution of sequence of the linear boundary value problems. On each step of iterative process for obtaining the numerical decision methods of R-functions and Ritz are used.
Keywords: уравнение теплопроводности; уравнение диффузии; задача Дирихле; метод R-функций; энергетический метод; метод Ритца; method of R-functions; method of Ritz; Dirichlet problem; Heat equation